Centers for Disease Control and Prevention 2015 Human Papillomavirus Vaccine Recommendations for Sexually Assaulted Patients: A Review and Update. Issue 4 (October 2016) - Scannell, Meredith
Abstract : ABSTRACT: Individuals who have been sexually assaulted are at risk for contracting human papillomavirus (HPV), the most common sexually transmitted infection. One of the best methods in protecting against contracting the HPV is to receive the HPV vaccine. To date, national sexual assault protocols and guidelines do not include information on HPV vaccination. The current 2015 Centers for Disease Control and Prevention has updated their recommendations for sexually assaulted patients to now receive the HPV vaccine. This article reviews information on HPV, HPV vaccines, and specific considerations for patients who have been sexually assaulted.